2010
DOI: 10.3758/app.72.8.2096
|View full text |Cite
|
Sign up to set email alerts
|

Attentional capture by motion onsets is modulated by perceptual load

Abstract: The onset of motion captures attention during visual search even if the motion is not task relevant, which suggests that motion onsets capture attention in a stimulus-driven manner. However, we have recently shown that stimulus-driven attentional capture by abruptly appearing objects is attenuated under conditions of high perceptual load. In the present study, we examined the influence of perceptual load on attentional capture by another type of dynamic stimulus: the onset of motion. Participants searched for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The results supported a perceptual load account of selective attention; and yet, a subsequent study-conducted in the same laboratory and using the same paradigm-showed that task-context could bias the results to support either perceptual load theory as postulated, or could show that salient distractors were fully processed under high perceptual load (Biggs & Gibson, 2010). Perceptual load has also been shown to modulate interference by salient abrupt onset stimuli (Cosman & Vecera, 2009, 2010a), yet a follow-up study qualified that evidence by showing the frequency of the abrupt onset could alter distractor processing under high perceptual load (Cosman & Vecera, 2010b). Both sets of results changed due to a specific influence that could interact with top-down expectations about the task.…”
Section: Discussionmentioning
confidence: 48%
“…The results supported a perceptual load account of selective attention; and yet, a subsequent study-conducted in the same laboratory and using the same paradigm-showed that task-context could bias the results to support either perceptual load theory as postulated, or could show that salient distractors were fully processed under high perceptual load (Biggs & Gibson, 2010). Perceptual load has also been shown to modulate interference by salient abrupt onset stimuli (Cosman & Vecera, 2009, 2010a), yet a follow-up study qualified that evidence by showing the frequency of the abrupt onset could alter distractor processing under high perceptual load (Cosman & Vecera, 2010b). Both sets of results changed due to a specific influence that could interact with top-down expectations about the task.…”
Section: Discussionmentioning
confidence: 48%
“…With respect to the current results, it is possible that increased inter-item competition in heterogeneous displays may engender stronger top-down control, ultimately leading to less distraction by salient, task-irrelevant information. This view is supported by a number of recent studies demonstrating reduced attentional capture in heterogeneous relative to homogeneous search arrays (e.g., Lamy & Tsal, 1999; Cosman & Vecera, 2009; 2010a; 2010b), as well as studies showing that other manipulations that influence local competition modulate the likelihood of distraction (Torralbo & Beck, 2008; Proulx & Egeth, 2006; Roper, Cosman, & Vecera, submitted). However, we don’t wish to argue that either explicit, strategic factors or differences in the scale of attention play no role in influencing attentional capture, but rather that that the attentional control system likely relies on multiple bottom-up and top-down factors that interact to determine capture in a given situation (see Cosman & Vecera, 2010a).…”
Section: Discussionmentioning
confidence: 78%
“…Other findings, however, indicate that such attentional capture only occurs for items that are task relevant; attentional capture is contingent on observer goals (Folk, Remington, & Johnston, 1992). Further, attentional capture is reduced under dual-task situations (Boot, Brockmole, & Simons, 2005) and in visually complex displays (Cosman & Vecera, 2009, 2010), two results that suggest that in-car alerts might do little to summon drivers’ attention because driving involves multitasking and searching complex visual scenes.…”
Section: Introductionmentioning
confidence: 99%